Improving of oat malt technology - Yemelyanova, Nina; Mukoid, Roman (My University, 2013)
Also was found that during malting of bare-grained oat content of biologically active substances increases significantly. Thus the content of fats and proteins decreases. Optimal technological parameters of bare-grained oats malting are as follows: temperature with a gradual increase from 14 to 17 °C, humidity 41…42 %, duration 4…4,5 days.
Keywords: oats; filmy; malt; malting; овес; плівчастий; солод; солодорощення; пленочный; солодоращение; кафедра біотехнології продуктів бродіння і виноробства